The Process of Early Childhood Character Building Through Parenting - Ismi Salsa Dina; Heri Yusuf Muslihin; Elan Elan (CV. Rayyan Dwi Bharata, 2023)
In this day and age, there are many children who have a personality or behavior that is very deviant and even apprehensive. This is due to the lack of attention from parents, people around and the surrounding environment which causes children to do whatever they want without filtering whether it is good or not for them. Therefore, with parenting from parents, children can become characters that are in accordance with the wishes of parents. For this reason, parenting is very important for children, because parents know and understand the child's condition and character and know the strengths and weaknesses of the child, so parents know what to do so that the child can become a good person. and according to the wishes of the parents.